2017
DOI: 10.1002/bit.26281
|View full text |Cite
|
Sign up to set email alerts
|

An artificial TCA cycle selects for efficient α‐ketoglutarate dependent hydroxylase catalysis in engineered Escherichia coli

Abstract: Amino acid hydroxylases depend directly on the cellular TCA cycle via their cosubstrate α-ketoglutarate (α-KG) and are highly useful for the selective biocatalytic oxyfunctionalization of amino acids. This study evaluates TCA cycle engineering strategies to force and increase α-KG flux through proline-4-hydroxylase (P4H). The genes sucA (α-KG dehydrogenase E1 subunit) and sucC (succinyl-CoA synthetase β subunit) were alternately deleted together with aceA (isocitrate lyase) in proline degradation-deficient Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Nevertheless, the deficiency of sucC in combination with aceA gene led to the carbon flux overflow to the acetate biosynthesis in E. coli (Theodosiou et al, 2017). Nevertheless, the deficiency of sucC in combination with aceA gene led to the carbon flux overflow to the acetate biosynthesis in E. coli (Theodosiou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, the deficiency of sucC in combination with aceA gene led to the carbon flux overflow to the acetate biosynthesis in E. coli (Theodosiou et al, 2017). Nevertheless, the deficiency of sucC in combination with aceA gene led to the carbon flux overflow to the acetate biosynthesis in E. coli (Theodosiou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the sucC-deficient E. coli ΔputA ΔaceA was able to grow in a glucose-minimal medium because the cells could obtain succinyl-CoA from α-ketoglutarate via α-ketoglutarate dehydrogenase and succinate from fumarate via fumarate reductase (Theodosiou et al, 2017). It was reported that the sucC-deficient E. coli ΔputA ΔaceA was able to grow in a glucose-minimal medium because the cells could obtain succinyl-CoA from α-ketoglutarate via α-ketoglutarate dehydrogenase and succinate from fumarate via fumarate reductase (Theodosiou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations